The Youth and Sexual Behavior: Media and Peer Influence Study: Pengaruh Media dan Teman Sebaya terhadap Perilaku Seksual Pranikah pada Remaja: Studi Lintas Penampang - Paramitha Amelia Kusumawardani (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the influence of media and peers on premarital sexual behavior among adolescents in both urban and rural areas. The research was conducted at Hizbul Wathan Kwarda Sidoarjo using a cross-sectional method. The study population consisted of 90 individuals who were members of Hizbul Wathan Scouts, and purposive sampling was employed for participant selection. A questionnaire was used as the research instrument. The findings revealed that the majority of participants (68 out of 90) had no exposure to media, and a significant proportion (63.3%) reported positive peer influence. Statistical analysis using Fisher's Exact test indicated that the influence of media on premarital sexual behavior was not significant (p-value = 0.219 > 0.05), whereas peer influence was found to be significantly associated with premarital sexual behavior (p-value = 0.000 < 0.05). These results suggest that while media exposure may not play a substantial role, peers exert a significant influence on premarital sexual behavior among Hizbul Wathan members. This study contributes to the understanding of factors shaping adolescent sexual behavior and highlights the importance of addressing peer influences in interventions aimed at reducing risky sexual behaviors among young individuals. Highlights: Media Influence: The study found no significant influence of media on premarital sex behavior among adolescents. Peer Influence: Positive peer influence was found to have a significant impact on premarital sexual behavior among adolescents. Cross-sectional Study: The research employed a cross-sectional method to investigate the relationship between media, peers, and premarital sex behavior among adolescents. Keywords: premarital sex, adolescents, media influence, peer influence, cross-sectional study